2005
DOI: 10.1097/00001888-200507000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Residents?? End-of-Life Decision Making with Adult Hospitalized Patients: A Review of the Literature

Abstract: Educational strategies aimed at changing residents' knowledge, skills and attitude should address the hidden curriculum for the patient EOL decision-making process that is part of the experienced culture of every day practice. Future studies of this experienced culture would inform specific educational interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 34 publications
1
58
0
Order By: Relevance
“…Second, the development and implementation of a clear and standardized DNR policy, accepted by all persons concerned and recognizing the important role of all professional caregivers (especially nurses), should be stimulated. Third, ongoing efforts should be made to change the knowledge, communication skills, and attitudes of professional health caregivers (physicians, nurses) (32). In addition, the general public should be made more familiar with this matter, for example, by health information programs.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the development and implementation of a clear and standardized DNR policy, accepted by all persons concerned and recognizing the important role of all professional caregivers (especially nurses), should be stimulated. Third, ongoing efforts should be made to change the knowledge, communication skills, and attitudes of professional health caregivers (physicians, nurses) (32). In addition, the general public should be made more familiar with this matter, for example, by health information programs.…”
Section: Discussionmentioning
confidence: 99%
“…39 In one survey of 155 medicine and surgery residents, 43% would withhold blood products and 32% would not give antibiotics to a patient with a DNR order. 40 Some believe that diagnostic tests should not be ordered when a patient is "DNR." This may be due to misunderstanding the scope of DNR orders by some providers.…”
Section: Problems With Dnr Orders In Practicementioning
confidence: 99%
“…It revealed that little is known about their training needs and experiences while caring for critically ill patients at EOL (Gorman et al 2005). An interview-based qualitative study was then conducted to identify what is important to physician trainees in ICU and infer on positive educational experiences for physician trainees.…”
Section: Introductionmentioning
confidence: 99%